“We Will not Get Another Chance if We Lose This Battle Now”: Populism on Ukrainian Television Political Talk Shows ahead of the Presidential Election in 2019 - Yanchenko, Kostiantyn (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
Against a background of increasing electoral support of populist political actors in Europe and beyond, this study offers an exploratory inquiry into modern Ukrainian populism. The article examines populist communication, broadcast on the most highly rated Ukrainian television political talk shows, on the eve of the 2019 presidential election, which was completed in two rounds. A qualitative content analysis of populist communication acts (n=283) shows that Ukrainian viewers were exposed to diverse political discourses containing empty, anti-elitist, emergency, and complete populism, depending on which channel(s) they watched. The dominance of one or another type of populism on the studied channels mirrors the dynamics of media-political parallelism typical of Ukrainian commercial television. The study also examines the roles of different actors—moderators, journalists, and politicians—in either restricting or facilitating populism in the talk show studios. The populism-related reactions collected during this analysis (n=145) are discussed through the prism of normative roles, with a focus on gatekeeping, interpretation, and initiation. Implications for the stakeholders involved in the process of production, moderation, and consumption of political talk shows are presented.